A phenylenediamine-mediated organic electrolyte for high performance graphene-hydrogel based supercapacitors. (20th May 2018) - Fang, Jianhui; Zhang, Xiangxin; Miao, Xiaofei; Liu, Yongchuan; Chen, Sujing; Chen, Yuanqiang; Cheng, Jian; Wang, Wei; Zhang, Yining
Abstract: We prepare a novel redox-additive organic electrolyte containing phenylenediamine for a graphene-hydrogel supercapacitor. By adopting this electrolyte, significant capacity enhancement (47–596% increase) is achieved. At the concentration of 0.02 mol l −1, the specific capacity value of the graphene-hydrogel electrode reaches 171 mAh g −1, 287 mAh g −1, and 353 mAh g −1 at 1 A g −1 for o-phenylenediamine (OPD), m-phenylenediamine (MPD), and p-phenylenediamine (PPD), respectively. The enhancement by PPD is more significant than OPD and MPD at concentrations higher than 0.02 mol l −1 . This behavior is likely caused by the para-amino groups, which exhibits less stereo-hindrance during the absorption of phenylenediamine onto the graphene surface. In the electrolyte containing 0.04 mol l −1 of PPD, specific capacity of 516 mAh g −1 at 1 A g −1 and energy density of 143 Wh kg −1 with power density of 1.11 kW kg −1 are achieved. Meanwhile, 93.8% of the electrode's initial capacity (433 mAh g −1 ) is retained after 5000 cycles at 2 A g −1, demonstrating its excellent cycling stability. Graphical abstract: Highlights: An organic redox-mediated electrolyte is prepared by adding phenylenediamine into 1 mol l −1 MeEt3 NBF4 acetonitrile solution. P-phenylenediamine enhances the specific capacity of graphene-hydrogel electrode more significantly than m-phenylenediamine and o-phenylenediamine. By adding 0.04 mol l −1 of p-phenylenediamine, the energy density of the graphene-hydrogel supercapacitor reaches 143 Wh kg −1 with power density of 1.11 kW kg −1 . With 0.04 mol l −1 of p-phenylenediamine, graphene-hydrogel electrode exhibits 93.8% capacity retention after 5000 charge-discharge cycles at 2 A g −1 .